INTERROGATING BASIC VALUES AND PRINCIPLES GOVERNING 'IDEALLY' PUBLIC ADMINISTRATION - Xolani Thusi; Modupi Selepe (Social Sciences and Education Research Review)
Section 195 of the Constitution of the Republic of South Africa, 1996, lays out the fundamental values and principles that should guide how the public sector operates to ensure a sustainable public sector and uninterrupted public service delivery. The South African government has been criticized for poor public service delivery, as evidenced by service delivery protests, which have become the norm in the public sector. South Africa, as a developing country, bears a burden in the public sector of citizens who rely on the government due to high unemployment, poverty, inequality, and an economy that does not provide economic benefits to citizens. The reality is that South Africans cannot escape poverty because of the country's stagnant economy, and the demand for service delivery will keep on rising and further burden the government that already has many deficiencies. The author, on the other hand, agrees that the South African government has had many accomplishments and landmarks over the years. Unfortunately, the government is no longer able to respond to every citizen's needs, and local government, as the sphere closest to the public, lacks the capacity to provide services to all local communities. The purpose of this paper is to examine how the government has failed to live up to Chapter 10 of the constitution, which specifies the ideal public administration in the country that could have met all citizens' basic needs as promised by the constitution. This paper contends that the fundamental values and principles that should guide how the public sector operates to ensure a sustainable public sector and uninterrupted public service delivery are just in the document and not in practice. The government has failed to maintain democratic governance and has failed the poor and vulnerable.